2021
DOI: 10.2196/25973
|View full text |Cite
|
Sign up to set email alerts
|

Turn on, Tune in, and Drop out: Predictors of Attrition in a Prospective Observational Cohort Study on Psychedelic Use

Abstract: Background The resurgence of research and public interest in the positive psychological effects of psychedelics, together with advancements in digital data collection techniques, have brought forth a new type of research design, which involves prospectively gathering large-scale naturalistic data from psychedelic users; that is, before and after the use of a psychedelic compound. A methodological limitation of such studies is their high attrition rate, particularly owing to participants who stop re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 89 publications
(108 reference statements)
3
12
0
Order By: Relevance
“…The concern of such dropouts is that they could create problematic biases in the data, with for example only those individuals experiencing benefits from the experience being motivated to continue responding to the questions. A recent study investigating potential determinants of study attrition in web-based prospective studies on psychedelic use identified that baseline predictors of attrition (i.e., age, educational levels, and personality traits) were consistent with those reported in longitudinal studies in other scientific disciplines, suggesting their transdisciplinary relevance (80). Moreover, they did not find an association between attrition and psychedelic advocacy or negative drug experiences, advocating against the concerns about problematic biases in these and related data.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The concern of such dropouts is that they could create problematic biases in the data, with for example only those individuals experiencing benefits from the experience being motivated to continue responding to the questions. A recent study investigating potential determinants of study attrition in web-based prospective studies on psychedelic use identified that baseline predictors of attrition (i.e., age, educational levels, and personality traits) were consistent with those reported in longitudinal studies in other scientific disciplines, suggesting their transdisciplinary relevance (80). Moreover, they did not find an association between attrition and psychedelic advocacy or negative drug experiences, advocating against the concerns about problematic biases in these and related data.…”
Section: Discussionmentioning
confidence: 91%
“…Finally, we ran an exploratory analysis (independent sample t -tests and chi-square tests) with a twofold purpose: (1) to examine if there are differences between psilocybin-naïve and experienced participants on the anxiety measures (both state and trait anxiety); (2) to assess attrition factors for variables that have previously found to be significant in similar studies [i.e., demographic variables and personality traits; ( 80 )], as well as study-specific factors of interest [i.e., baseline anxiety levels (state and trait) and acute drug effects (EDI scores)].…”
Section: Methodsmentioning
confidence: 99%
“…Greater efforts should be made in future studies to both minimise attrition rates and assess what factors are contributing to them, as done here (Hübner et al, 2021). Fortunately, initial explorations of potential attrition bias in the present datasets have generally been reassuring.…”
Section: Discussionmentioning
confidence: 99%
“…This question is important, not least because of considerations of efficiency in the design of future studies, where, for example, the number of questionnaires could be reduced to just a few, sensitive but sufficiently orthogonal and therefore complementary ones. This issue is particularly relevant in prospective web-based surveys where high attrition rates due to participant burden are a common problem (84,106).…”
Section: Discussionmentioning
confidence: 99%